E-Module Speaking Based Gamification to Improve Students’ Intercultural Understanding - Hanifah Hanifah; Elsa Ernawati Ninggolan (Jurnal Paedagogy, 2023)
This study aims to develop a "gamified" e-module so that students' intercultural understanding improves in the Speaking for General Communication course. The subjects of this study were students in the second semester of the English Education study program at Universitas Maritim Raja Haji. This research used the Research and Development method with Thiagarajan's 4D model, which had been modified to 3D (define, design, and development). This research instrument used interviews, student questionnaires, and validation forms. The data analysis techniques of this research were descriptive analysis and descriptive statistics. Based on the findings of the first stage, it was determined that an e-module for the speaking course was required because there were no learning resources developed specifically for online classes and the existing learning source was insufficient for the student's current needs. Based on the analysis results, e-module topics, language features, and learning objectives were determined. In the second stage, the e-modulus was designed with four components: cover, introduction, content section, and closing section. In the final stage, the e-module validation results showed that the speaking e-module for general communication was valid and could be used in an online class.